Engineered microorganisms for bioremediation in aquatic ecosystems for pollution mitigation - Aliev, Sarvar; Hasan, Montader M.; Sayyorakhon, Khabibullayeva; Kizi, Makhamadali; Gopinath, Praveen Kumar; Dewangan, Tripti (International Journal of Aquatic Research and Environmental Studies, 2025)
Aquatic ecosystems are under immense threat from hydrocarbons, heavy metals, pesticides, microplastics, and other anthropogenic pollutants. Traditional pollutant removal techniques are not able to achieve sustainable results and cause ecological harm. This research proposes a different bioremediation solution that uses genetically engineered microorganisms to refine pollutant degradation, stabilization, and specificity in water. This study proposes a different bioremediation solution by genetically engineered microorganisms to refine degradation, stabilization, and specificity to pollutants in water. By integrating synthetic biology and omics-based pathway optimization along with other bioinformatics tools, the researcher aims to develop pollutant-degrading microorganisms adapted to different aquatic conditions. The proposed engineered microbial bioremediation system (EMBS) consists of a detailed multi-phase system which includes (i) characterization of the pollutant and identification of target genes, (ii) CRISPR-Cas9 genome editing to add and enhance the catabolic pathways, (iii) bioreactor validation for degradation kinetics, and (iv) mesocosm-scale testing for ecological safety and performance under quasi-natural settings. Compared to wild-type strains, experimental results show over 80% reduction in hydrocarbons and nitrates in a 72-hour period. These results showcase EMBS as a highly effective, sustainable, and flexible method for the removal of pollutants in aquatic systems. Different bioremediation EMBS techniques can be used to target pollutants and strengthen the bioeconomy. Environmental policy can also target active pollutants to strengthen the EMBS bioeconomy.